Peran Pemerintah Terhadap Usaha Mikro Kecil Menengah Perempuan Di Kota Bukittinggi - Handrina, Emi (CV. ITTC INDONESIA, 2025)
With the issuance of PP Number 47 of 2024, it shows that the government is present for MSMEs, and provides opportunities for women as MSME actors to be more productive and strengthen their competitiveness in the market. Empowering women in supporting MSMEs has enormous potential and must be optimized by the central government and local governments. It is important to have cooperation from various parties such as the private sector, banking and other institutions to support women's empowerment. To improve the economy of women in Bukittinggi, the Bukittinggi City Government in 2023 through the Women's Empowerment, Child Protection, Population Control and Family Planning Service (DP3APPKB) held culinary training to improve women's MSMEs in Bukittinggi City.